Power, process and participation : (ITDG, 1995)
This book focuses on participatory capacity-building in ways that address the practical needs and strategic interests of the disadvantaged and disempowered - it examines how differences in class, ethnicity, race, caste, religion, age and gender lead to the politics of exclusion. It offers innovative, accessible tools to enable facilitators from both inside and